Coping Strategies as a Mediator of Posttraumatic Growth among Adult Survivors of the Wenchuan Earthquake - He, Lili (Public Library of Science, 2013)
OBJECTIVE: By testing the mediating effect of coping strategies on the relationship between social support (SS) and posttraumatic growth (PTG), the aim of this research was to develop a new approach for the study of post-disaster psychological intervention. METHODS: A mediating effect model analysis was conducted on 2080 adult survivors selected from 19 of the counties hardest-hit by the 2008 Wenchuan earthquake. The Social Support Rating Scale and the Coping Scale were used to predict the PTG. RESULTS: A bivariate correlation analysis showed that there was a correlation between posttraumatic growth, social support and coping strategies. The mediation analysis revealed that coping strategies played a mediating role between social support and posttraumatic growth in survivors after the earthquake. CONCLUSION: The results demonstrated that mental health programs for survivors need to focus on the establishment of a good social support network, which was found to be conductive to maintaining and increasing mental health levels. At the same time, adequate social support is able to assist survivors in adopting mature coping strategies, such as problem solving and asking for help. Hence, social support was found to play a vital role in balancing and protecting mental health.